1932
DOI: 10.3181/00379727-29-6114
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance of Carbohydrate Metabolism in Normal Dogs Injected with the Hypophyseal Growth Hormone.

Abstract: Clinical and experimental data have been accumulating indicating a functional relationship between the anterior lobe of the hypophysis and the pancreatic islets.Due to the importance of such a relationship we think it justifiable to note briefly some remarkable findings bearing on this matter.Two litters of purebred dachshund, one consisting of 2 males, the other of 2 females were secured. One male and one female were injected daily intraperitoneally with the anterior hypophyseal growth hormone,t free of gonad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1933
1933
1999
1999

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Houssay, 1 -2 Evans, 3 and Young 4 first demonstrated the diabetogenic effect of growth hormone (GH). A comprehensive review on the subject was published by Sirek and Sirek.…”
mentioning
confidence: 99%
“…Houssay, 1 -2 Evans, 3 and Young 4 first demonstrated the diabetogenic effect of growth hormone (GH). A comprehensive review on the subject was published by Sirek and Sirek.…”
mentioning
confidence: 99%
“…Evans et al [2] subsequently found diabetogenic activity in an anterior pituitary extract and attributed it to growth hormone. Four years later Lyall and Innes [3] reported a case of dia betes mellitus in man where the development of hypopi tuitarism led to an amelioration of the metabolic state.…”
Section: Historical Introductionmentioning
confidence: 99%
“…Significant abnormalities in blood sugar were not observed at any time intervals in the partial or sham pancreatectomized groups. Respective values for blood sugar in these groups were 84 mg per 100 ml [2] and 58 ± 4 mg per 100 ml [5] 5 hours following surgery, and 107 ± 5 mg per 100 ml [4] and 102 + 6 mg per 100 ml [13] at sacrifice.…”
Section: (Carbohydrate Metabolism Of Surviving Anteriormentioning
confidence: 90%